Superconductivity : Theory and Applications - Moyses Luiz, Adir; Moyses Luiz, Adir (IntechOpen, 2011)
Superconductivity was discovered in 1911 by Kamerlingh Onnes. Since the discovery of an oxide superconductor with critical temperature (Tc) approximately equal to 35 K (by Bednorz and Muller 1986), there are a great number of laboratories all over the world involved in research of superconductors with high Tc values, the so-called "High-Tc superconductors". This book contains 15 chapters reporting about interesting research about theoretical and experimental aspects of superconductivity. You will find here a great number of works about theories and properties of High-Tc superconductors (materials with Tc > 30 K). In a few chapters there are also discussions concerning low-Tc superconductors (Tc < 30 K). This book will certainly encourage further experimental and theoretical research in new theories and new superconducting materials.
English
Keywords: Spectrum analysis, spectrochemistry, mass spectrometry; Electrochemistry & magnetochemistry